2007
DOI: 10.1080/00016340701286793
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel node and vulvar cancer: a series of 47 patients

Abstract: A sentinel node identification rate of 98% with a false-negative rate of 0% in the patients with Stage I-II disease is an encouraging finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…Many authors have reported the use of a combination of technetium and blue dye for the SLNB procedure in vulvar CA [25,[32][33][34][35][36][37][38][39][40][41][42]. Rationale behind this practice relates to the importance of identifying the SLNs intra operatively.…”
Section: Slnb Techniquementioning
confidence: 99%
“…Many authors have reported the use of a combination of technetium and blue dye for the SLNB procedure in vulvar CA [25,[32][33][34][35][36][37][38][39][40][41][42]. Rationale behind this practice relates to the importance of identifying the SLNs intra operatively.…”
Section: Slnb Techniquementioning
confidence: 99%
“…Under a 4.5-year familiarization period, a SLN mapping had been performed to all surgically treated vulvar cancer patients, and has been described elsewhere [17]. The specimens were obtained from the Tissue Biobank and Research Services FinTiB (Fimlab Laboratories Inc., Tampere, Finland).…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…Studies in vulvar cancer in which SLN detection was followed by a completion inguinofemoral lymphadenectomy suggest that the SLN procedure is highly accurate in identifying lymph node metastases with an NPV approaching 100% [24,25,29,30,38,40,[65][66][67][68][69][70][71][72][73]. Table 1 illustrates selected studies on this subject.…”
Section: Squamous Cell Vulvar Carcinomamentioning
confidence: 99%